A novel self‐timing CMOS first‐edge take‐all circuit for on‐chip communication systems - Saleh Abdelhafeez; Shadi M. S. Harb (IET Computers & Digital Techniques)
Abstract In today's communication systems, it has become prominent for processing elements (PEs) to receive requests with simultaneous, conflicting signals, which are unpredicted and randomly triggered. In such a case, multiple overlapping signal requests can potentially compete in the same PE causing erroneous operations or a halt of the communication cycle. The authors propose a self‐timing CMOS first‐edge take‐all (FETA) circuit architecture, which examines two overlapping signals’ requests, and outputs only the leading‐edge signal while the lagging‐edge signal's request is declined. The FETA circuit functionality is considered as an essential component in First‐In‐First‐Out for metastability avoidance, which usually occurs between the write and read overlapping requests for applications related to Internet of Things, Network‐on‐Chips, and microprocessor memory management units. HSPICE simulations for a 90 nm CMOS technology are used to verify the speed up to 1 GHz. Besides, the achievable resolution is in the order of 20 ps considering process variation sensitivity based on design inheriting symmetric timing paths between the two signals. Additionally, the proposed circuit architecture adopts a self‐timing scheme obviating the overhead synchronisation circuitry, which comprises 12 D‐Type Flip‐Flops with about 300 transistors. This design is suited for HDL synthesis and FPGA application features.